You could do the question the way it is written, but it is far easier to bring the negative power up to the numerator.
y= x^2 - 3. The derivative of that is
dy/dx = 2x The three is a constant and is always dropped when a derivative is taken
d(-3)/dx = 0
If you are a purist and want to solve the question the way it is written, you could do it this way.
dy/dx = d(1)/dx x^-2 - d(x^-2)/dx * 1
======================
(x^-2)^2
dy/dx = - (-2 x^ - 3) / x^-4
dy/dx = 2 x^-3 * x^4
dy/dx = 2 x^(-3 + 4)
dy/dx = 2x ^ 1
dy/dx = 2x <<<<< answer
Answer:60
Step-by-step explanation:
a=13 b=13 c=10
Perimeter of =a+b+c
perimeter of =13+13+10
Perimeter of =36
S=36 ➗ 2
S=18
Area=√s(s-a)(s-b)(s-c)
Area=√18(18-13)(18-13)(18-10)
Area=√18(5)(5)(8)
Area=√(3600)
Area of =60
Answer:
positve and linear realationship
Step-by-step explanation:
Log_3(x(x + 24) = 4
log_3(x^2 + 24x) = 4
3^4 = (x^2 + 24x)
81 = x^2 + 24x
x^2 + 24x - 81 = 0
Continue from here.